SOME ECONOMIC ASPECTS OF LEGISLATION OF THE EUROPEAN UNION ON TRADE WITH POLLUTION PERMITS - Popov, Đorđe (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Abstract: Introduction emphasizes that the paper deals with the analysis of the economic effects of the EU Directive on trade with pollution permits. The ideas of ​​trading with pollution permits have their theoretical origins in the economic analysis of law. The second part provides an overview of the two main trading systems with pollution permits. In one system is limited the total mass of pollution that can be traded. This system is essentially a pure tradable permit system. The second system is based on trade with pollution reductions in the future. This section, also pointed out the existence of the possibility for manipulation with the market for pollution permits. There is also a review of basic forms of manipulation. The third part is dedicated to a comparative analysis of the effectiveness and efficiency of various trading systems for pollution permits. Special attention is given to the impact of the opportunity cost on preferences by certain companies. In the fourth part the paper analyzes the Directive of the European Commission 2003/87 and 2009/29 on trade with pollution permits, and the expected results in the reduction of pollution for each of them. The fifth part of the paper predicting the behavior of companies within the EU as a result of the Directive 2003/87 and 2009/29. In the sixth and final section paper concludes that: trade with pollution permits can be an effective instrument in the battle against environmental pollution. But unfortunately sometimes could produce unintended results.